Endothelial Cells Promote Osteogenesis by Establishing a Functional and Metabolic Coupling With Human Mesenchymal Stem Cells - Petrillo, Sara; Genova, Tullio; Chinigò, Giorgia; Roato, Ilaria; Scarpellino, Giorgia; Kopecka, Joanna; Altruda, Fiorella; Tolosano, Emanuela; Riganti, Chiara; Mussano, Federico; Munaron, Luca (Frontiers in Physiology, 2022)
Bone formation involves a complex crosstalk between endothelial cells (EC) and osteodifferentiating stem cells. This functional interplay is greatly mediated by the paracrine and autocrine action of soluble factors released at the vasculature-bone interface. This study elucidates the molecular and functional responses triggered by this intimate interaction. In this study, we showed that human dermal microvascular endothelial cells (HMEC) induced the expression of pro-angiogenic factors in stem cells from human exfoliated deciduous teeth (SHED) and sustain their osteo-differentiation at the same time. In contrast, osteodifferentiating SHED increased EC recruitment and promoted the formation of complex vascular networks. Moreover, HMEC enhanced anaerobic glycolysis in proliferating SHED without compromising their ability to undergo the oxidative metabolic shift required for adequate osteo-differentiation. Taken together, these findings provide novel insights into the molecular mechanism underlying the synergistic cooperation between EC and stem cells during bone tissue renewal.